2013
DOI: 10.3390/ijerph10115683
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of Selected Physical Exercise Programs in Detention: A Randomized Controlled Study

Abstract: The aim of the study was to determine which kind of physical activity could be useful to inmate populations to improve their health status and fitness levels. A repeated measure design was used to evaluate the effects of two different training protocols on subjects in a state of detention, tested pre- and post-experimental protocol.Seventy-five male subjects were enrolled in the studyand randomly allocated to three groups: the cardiovascular plus resistance training protocol group (CRT) (n = 25; mean age 30.9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
32
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(45 citation statements)
references
References 35 publications
(40 reference statements)
6
32
0
7
Order By: Relevance
“…One explanation for these differences is that the team setting of rugby provided a sense of belonging and team membership for the intervention participants, whilst the no intervention participants found this sense of belonging in gang membership. This is consistent with research that has studied the potential for team sports to bring people together (Thorpe et al, 2014), especially those who are at risk of gang-affiliation (Spruit et al, 2018) with the positive relationship between a good support system and wellbeing well documented (Battaglia et al, 2013).…”
Section: Social Influences and Cohesion Through Rugbysupporting
confidence: 87%
See 2 more Smart Citations
“…One explanation for these differences is that the team setting of rugby provided a sense of belonging and team membership for the intervention participants, whilst the no intervention participants found this sense of belonging in gang membership. This is consistent with research that has studied the potential for team sports to bring people together (Thorpe et al, 2014), especially those who are at risk of gang-affiliation (Spruit et al, 2018) with the positive relationship between a good support system and wellbeing well documented (Battaglia et al, 2013).…”
Section: Social Influences and Cohesion Through Rugbysupporting
confidence: 87%
“…In line with the increasing number of interventions being provided in prisons to meet rehabilitation needs, recent research has examined the social, psychological and health benefits of prisonbased programs which include those focusing on arts, horticulture and vocational activities (Farrier et al, 2019;Wilkinson and Caulfield, 2017). The majority of these studies have demonstrated benefits in quality of life and reduced anxiety, depression and stress (Battaglia et al, 2013) as well as reduced rates of recidivism (Proctor et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The motor skills formed at previous stages are consolidated and even improved, being integrated in various types of educational, motor, leisure and competitive activities etc. [3,5,6].…”
Section: спортивная тренировкаmentioning
confidence: 99%
“…Recent study results suggest that physical activity seems to improve prisoners' fitness and health status by reducing their health care needs and associated public spending [7]. Moreover, physical activity and continuous vocational training during incarceration are considered very useful for leisure time activities and for social reintegration encouragement after release [7][8][9].…”
Section: Introductionmentioning
confidence: 99%